Optimalisasi Pemberdayaan Masyarakat Berbasis Potensi Desa Wisata di Kabupaten Buton Selatan - Anwar Sadat; Nastia Nastia; Hastuti Hastuti (Empowerment : Jurnal Pengabdian Masyarakat, 2021)
Tourism village is a community empowerment initiative that aims to maximize the potential of the village in order to increase the welfare of its citizens. This community service activity aims to identify the types of community empowerment actions contained in the tourism village program. This service aims to provide local wisdom and natural resources to villages that have the potential to become tourist destinations. This activity was carried out with local village government partners to get to know and grow the village's potential with the help of youth from the Youth Organization. The form of community service used by ABCD (Asset Based Community Development) is used to seek tourism innovation on existing village assets / potentials to improve the standard of living of the community. Community empowerment is tried by maximizing the tourism village program to become a potential-based tourism commodity. Tourism Village has provided a transformation to take on increasing knowledge and the community's economy.